ARABIC PHONOLOGY - Zulaika, Siti; Suryani, Agustina (Yayasan Haiah Nusratul Islam, Indonesia, 2025)
The study of language has a significant impact on human existence. Like two sides of a coin, language and life are inextricably linked phenomena. Words are a system of arbitrary sound symbols that people use to talk to one another. Language is a system with both systemic (subsystem) and systematic (methodical) properties. Phonology is one of the subsystems. One of the branches or levels of linguistics that covers all things relating to sounds is phonology. Words There are two categories for this language's sounds: phonetics and phonemic. As a subfield of phonology, phonetics examines related language sounds that do not alter meaning, whereas phonemes examine language sounds that do This essay aims to investigate Arabic phonology, namely the phoneme component. For Arabic language learners, the first thing they need to acquire is the language's sound. As a result, studying phonology is crucial for language acquisition and proficiency (foreign language). As a result, it becomes crucial to comprehend phonological research, or al-Aswa>t, in order to gain a thorough comprehension of Arabic language sounds, each of which naturally has a unique meaning.